Financial Abuse of Elderly People vs. Other Forms of Elder Abuse in Virginia, 2003-2008 - Jackson, Shelly L. ([Verlag nicht ermittelbar], 2015)
This study examined financial exploitation of elderly people compared to other forms of elder maltreatment (physical abuse, neglect, and hybrid, i.e., financial exploitation and physical abuse and/or neglect) that occurred in a domestic setting. The cases were explored by obtaining information from a variety of sources including: Three different individuals about a given case including (1) the caseworker from APS that managed the reported case, (2) the person who had been reported to have experienced elder abuse and, (3) where they were available, a non-offending third party who knew the elder at the time of the APS response to the report of elder abuse (e.g., the elder's domestic partner, care provider, friend, or family member). Data derived from the Virginia Department of Social Services' Adult Services Adult Protective Services (ASAPS) Database which contains information drawn from several sources. Prosecutors in four states that were interviewed about their experience prosecuting elder abuse, barriers and facilitators associating with prosecuting such cases, and possible reforms. The specific goals of this research were to (1) Determine unique aspects of financial exploitation as compared to other forms of elder maltreatment, including risk factors, reporting, investigation, and case outcomes; (2) Determine the degree of congruence between the perceptions of victims of elder maltreatment and APS caseworkers regarding these cases; and (3) Develop recommendations based on these findings for addressing the financial abuse of the elderly.